'Independence 2.0': Digital activism, social media and the Catalan independence movement. Issue 2 (1st October 2019) - Anderson, Paul
This article examines the role and use of social media in the ongoing movement for Catalan independence by focusing on two pro-independence civil society organizations, Feministes per la Independència (FxI) and Òmnium Cultural (OC). Drawing upon elite interview data with representatives from both organizations and Catalan parliamentarians, it posits that social media platforms serve as crucial vehicles for these civil society organizations, particularly in terms of empowerment, mobilization, organization, participation and resistance. The increasing salience of digital activism in Catalonia is such that social media platforms have become fundamental pillars of the independence movement, helping to overcome state-imposed institutional obstacles as well as internationalize the issue across transnational networks. The analysis, however, also reveals a darker side to engagement with social media including the proliferation of biased narratives, dissemination of misinformation and trolling. On the basis of these reflections, the article concludes that while engagement with social media entails risks, hitherto such platforms have proved to be highly effective and will continue to be pivotal in promoting and generating support for the independence cause.